PENGARUH MODEL PEMBELAJARAN SNOWBALL THROWING TERHADAP MINAT BELAJAR GEOGRAFI KELAS XI IIS SMA NEGERI 1 TUMPANG KABUPATEN MALANG - Endang Wijaya Tri Pamungkas; Sudarno Herlambang; Juarti Juarti (Jurnal Pendidikan Geografi, 2016)
Abstract: This study aims to describe the influence of the Snowball Throwing learning model toward the learning interest of student of State Senior High School of 1 Tumpang in the subject of geography. This research is a quasy experiment with pretest-posttest only control group design in the form of student interest in the subject of geography and snowball throwing learning model. The sample of this research was taken from class of XI IIS 1 as the controlled class of 26 students and the class of XI IIS 2 as the experimental class of the 27 students. The instrument of this research a questionnaire of geographic learning interest that is consisting of a questionnaire of pre test and post test. Based on result of the research that was any different interest between the experiment class which using a snowball throwing learning model and control class which using lecture and debriefing with sig (2-tailed) 0,000 < 0,05, so H0 is defused and H1 is accepted which mean that any difference of geographical learning interest control class and experiment class. The average score of gain score on experiment class is higher than the control class, namely 16,59 > 3,08, it indicates there is effect of snowball throwing learning model to the geographical learning interest of student XI IIS at State Senior High School of 1 Tumpang.Key Word: Snowball Throwing, Learning Interest.